Factors affecting gen Y’s purchase intention of online shares: the fusion of online financial communication and social impact branding as an integrated marketing communication strategy - De Costa, Mohd Feroz Shah (Asian Scholars Network, 2020)
The objective of this study is to determine the effect of disseminating financial information via user generated content and firm generated content on millennials’ purchase intention of Shariah-compliant shares. A convenience sampling procedure using online questionnaires from millennials in Malaysia was used to test seven hypotheses based on prior literature. The partial least squares structural equation modelling (PLS-SEM) technique was used to analyse this study. The findings of this study indicated that user generated content and firm generated content positively influence brand attitude. By applying the signalling theory, the result showed a contradictive outcome to previous literature. User generated content has no direct effect on the purchase intention of Shariah-compliant online stocks. Theoretical and managerial implications of online financial communication and social impact branding as an integrated marketing strategy are discussed.